Evaluación de niveles de fertilización fosforada en el macollamiento y rendimiento del cultivo de arroz (oryza sativa l.) En condición de campo. - Arreaga Olvera, Oscar Sebastián (2023)
This research was conducted at the Technical State University of Quevedo, Faculty of Livestock and Biological Sciences, La María Campus. The main objective was to evaluate phosphorus fertilization levels on tillering and yield of rice cultivation under field conditions. Four treatments were employed: T1 (Control or reference), T2 (1L/ha-1), T3 (1.5 L/ha-1), T4 (2 L/ha-1). These treatments were distributed using a Completely Randomized Block Design (CRBD) with four replications. The evaluated variables included plant height (cm), number of tillers, panicles at harvest, panicle length, grains per panicle, 1000-grain weight (g), yield (kg), and economic analysis. Regarding agronomic, reproductive, and productive variables, there were no statistical differences. Finally, an economic analysis of the studied treatments was conducted, determining that treatment T4 achieved a higher B/C ratio with a net gain of 6.66 dollars for every dollar invested